ENGLISH (CIPEEX, 2022)
THE DIGITAL INCLUSION PROJECT EMERGED WITH THE IMMINENT NEED TO INCLUDE A CERTAIN AUDIENCE WHOSE DIFFICULTY IS DEALING WITH CONSTANT TECHNOLOGICAL EVOLUTIONS. ID IS CENTERED ON BEING AN INTERCOMMUNICATOR BETWEEN THE TYPE OF INNOVATION AND THE USER, WHERE THROUGH RESEARCH FOCUSED ON A CERTAIN SUBJECT, IT WILL ANSWER YOUR QUESTIONS THROUGH SHORT AND SUBTITLED TUTORIALS. THE APPLICATION WILL HAVE A COLLABORATORS SYSTEM, A SYSTEM THAT WILL WORK THROUGH A RECRUITMENT LINK, WHERE PEOPLE WHO MAKE THEMSELVES AVAILABLE WILL HAVE THE OPPORTUNITY TO BE PART OF THE ID COMMUNITY, HELPING TO GENERATE EDUCATIONAL VIDEOS THAT WILL DRIVE TECHNOLOGICAL ADVANCES DAILY. DAY OF THOSE WHO, BEFORE ID, WERE UNABLE TO CARRY OUT ESSENTIAL ACTIVITIES IN TODAY'S GLOBALIZED WORLD. TO ORIGINATE THE CONTENT, THE COLLABORATORS WILL HAVE A SYSTEM OF THEMES PROPOSED BY THE USERS OF THE PLATFORM, WHICH WILL BE LEFT IN A FIELD OF SUGGESTIONS (THESE THEMES MUST BE RELATED TO THE DIGITAL WORLD), AND BY REPORTS THAT WILL BE ISSUED BY THE FEEDBACKS RECEIVED. AT THE END OF EACH VIDEO. TO VOLUNTEER, AN INDIVIDUAL MUST MEET CERTAIN REQUIREMENTS PROPOSED AT THE TIME OF APPLICATION. TO SEND THE TUTORIALS, IT WILL BE NECESSARY TO UNDERGO AN EVALUATION OF THE CONTENT TO VERIFY THE HARMFULNESS OF THE SAME, AND A SIGNATURE AGREEING WITH THE ETHICAL AND MORAL TERMS OF "DIGITAL INCLUSION". FOR THE CREATION OF THE MOBILE APPLICATION, THE MAPPING OF PERSONAS, QUALITATIVE RESEARCH, WIREFRAMES AND INFORMATION ARCHITECTURE PROCESSES WERE DEVELOPED THROUGHOUT THE SEMESTER. ALL THESE STEPS WERE THOUGHT OUT AND DEVELOPED AFTER MEETINGS WITH THE SQUAD AND INTERVIEWS WITH POSSIBLE BENEFICIARIES OF THE MOBILE APPLICATION, WHICH GUIDED THE PROJECT TOWARDS A PATH OF GREATER USABILITY, ACCESSIBILITY AND RELIABILITY. LAWS WERE ALSO IMPLEMENTED, SUCH AS USABILITY AND AESTHETIC EFFECT, AIMING TO DELIVER A CLEAN AND PUNCTUAL APPLICATION, THE FITTING LAW THAT WILL BE APPLIED THROUGH EXPLICIT AND WELL-LOCATED FEATURES, AND THE ZLIGARNIK PRECEPT THAT WAS IMPLEMENTED ON THE APPLICATION'S HOMEPAGE, WITH VIDEOS IN ROTATING FORMAT. THE APPLICATION ALSO HAS A COLOR PALETTE AIMED AT USER CONFIDENCE AND SECURITY, THUS USING VARIATIONS OF BLUE. INTERFACE PROTOTYPES WERE DESIGNED TAKING INTO ACCOUNT FACTORS SUCH AS FUNCTIONAL REQUIREMENTS AND THE NEEDS OF THE TARGET AUDIENCE. FINALLY, IT IS CLEAR THAT ID PROVES TO BE A WELL-STRUCTURED PROJECT, CAPABLE OF INCLUDING PEOPLE IN THE DIGITAL ENVIRONMENT, ESPECIALLY THOSE WHO DID NOT OBTAIN THE NECESSARY INFORMATION AND OPPORTUNITIES TO FACE THE CONSTANT EVOLUTION OF TECHNOLOGY.